Cardioprotective effect of Trichopus zeylanicus against myocardial ischemia induced by isoproterenol in rats - Sivanandham Velavan, S. Selvarani and A. Adhithan (Bangladesh Pharmacological Society, 2009)
The cardioprotective effect of Trichopus zeylanicus leaves against isoproterenol-induced myocardial ischemia was studied. Wister strain rats were pretreated with T. zeylanicus leaves (500 mg/kg body weight) for 28 days and then intoxicated with isoproterenol (20 mg/100 g, i.p. for 2 consecutive days). Cardioprotection was assessed by estimating plasma and heart aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, and creatine phosphokinase. Troponin T was estimated in serum, and the levels of thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH) were analyzed in heart and plasma. In isoproterenol-treated group, shrinkage of cardiac markers in plasma and elevated lipid peroxidation were accompanied by decreased content of reduced glutathione in heart and plasma. The prior administration of T. zeylanicus significantly (p<0.001) prevented the isoproterenol-induced alterations and restored the cardiac markers. These findings indicate the cardioprotective activity of T. zeylanicus during isoproterenol-induced myocardial ischemia.